2018
DOI: 10.1111/tpj.14065
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization‐facilitated genome merger and repeated chromosome fusion after 8 million years

Abstract: The small genus Ricotia (nine species, Brassicaceae) is confined to the eastern Mediterranean. By comparative chromosome painting and a dated multi-gene chloroplast phylogeny, we reconstructed the origin and subsequent evolution of Ricotia. The ancestral Ricotia genome originated through hybridization between two older genomes with n = 7 and n = 8 chromosomes, respectively, on the Turkish mainland during the Early Miocene (c. 17.8 million years ago, Ma). Since then, the allotetraploid (n = 15) genome has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 64 publications
4
18
0
Order By: Relevance
“…Biscutella and Megadenia in the early Miocene (ca 18.75 Mya) is fully congruent with recent estimation ofMandáková et al (2018), who placed it about 24.75-17.9 Mya (with crown at 21.67 Mya).…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Biscutella and Megadenia in the early Miocene (ca 18.75 Mya) is fully congruent with recent estimation ofMandáková et al (2018), who placed it about 24.75-17.9 Mya (with crown at 21.67 Mya).…”
supporting
confidence: 89%
“…Biscutella, with the chromosome basic number x = 6 having appeared early in the evolution of the series, very likely following a dysploidy event (the remaining sections and series are x = 8, 9). This pattern might parallel the genome evolution shown by Mandáková et al (2018) Hsü et al 1973Hsü et al , 1978Bocquet et al, 1978;Krijgsman et al, 1999). The Iberian and African plates remained connected about 0.6 million years through a temporal bridge along the Betic-Rifan Arc (cf.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Biscutella with the chromosome basic number x 5 6 being the probable result of dysploidy in the early evolution of the series (the remaining sections and series are x 5 8, 9) (see Alonso et al, 2020). Similar patterns of genome evolution have recently been reported by Mandáková et al (2018) in the related Ricotia, a genus in which descendant dysploidy played an important role in cladogenesis.…”
Section: Discussionmentioning
confidence: 60%
“…Comparative genomics and chromosome painting revealed that the ancestral karyotype of the Lineage I, the Ancestral Crucifer Karyotype (ACK), was comprised of eight chromosomes (n = 8) and 22 genomic blocks (GBs) (Lysak et al, 2016). The inferred ancestral karyotype of the Lineage II, the 'Proto-Calepineae Karyotype' (PCK, n = 7; Mandáková et al, 2018;Mandáková & Lysak, 2008), was found to be derived from the ancestral PCK (ancPCK, n = 8) through descending dysploidy, namely a reduction in chromosome number (Geiser et al, n.d.;Mandáková et al, 2018).…”
Section: Introductionmentioning
confidence: 99%